Audio encryption using two chaotic map based dynamic diffusion and double DNA encoding. (28th February 2023) - Kumar, Atul; Dua, Mohit
Abstract: A large amount of data in the form of audios are communicated all over the world. However, the attacker can steal this data, and then misuse this information. Hence, it is necessary to create strong audio encryption strategy to protect the data from various types of existing threats. This paper discusses about the implementation of a novel chaos-based strategy for audio encryption that uses the Sine-Cosine (SC) Map, Logistic Sine Cosine (LSC) map, and double DNA operation. The proposed approach is divided into three parts, i.e., Firstly, the permutation is performed using the Sine-Cosine map to generate the permuted audio. The permuted audio samples are scrambled using the double DNA addition encoding in the second phase. Finally, dynamic diffusion is carried out by selecting one of the chaotic maps from SC Chaotic map and the LSC map. The evaluation of the proposed approach has been done using various standard metrics like Peak Signal to Noise Ratio (PSNR), Histogram Analysis, Number of Sample Change Rate (NSCR), Correlation Coefficient (CC).